Needs analysis of interactive STEM-based multimedia to enhance literacy and 21st-century skills - Widya, Widya; Mujtahid, Zainul; Muliaman, Agus; Hidayat, Amam Taufiq (Universitas Islam Negeri Raden Intan Lampung, 2024)
Learning media development should integrate interactive features with engaging, real-world content. This study aims to analyze the need for interactive multimedia based on STEM (Science, Technology, Engineering, and Mathematics) education to enhance literacy skills and 21st-century competencies. The study employs a qualitative approach using a needs analysis method, involving data collection through in-depth interviews with teachers and curriculum document analysis. The results indicate that students require learning media that are engaging, relevant to their daily lives, and capable of fostering literacy and 21st-century skills. On the other hand, teachers highlight the need for practical, accessible learning media that can enhance student engagement in the learning process. These findings emphasize the importance of developing interactive multimedia based on STEM education to support more effective learning. This study implies the need for innovations in developing interactive STEM-based learning media that align with modern educational demands.